Bilateral Paget's Disease of the Breast-Case Report of Long-Time Misdiagnosed Tumors with Underlying Ductal Carcinomas and Review of the Literature - Dietrich Barth (Hindawi Limited, 2014)
Paget's disease of the breast is often misdiagnosed. We report on a 72-year old patient with a history of 2.5 years without any malignant findings, followed by the identification of a bilateral Paget's disease with bilateral breast cancers. This case underlines how important histological examinations even in unusual clinical pictures are.